A new species of Leucostethus (Anura: Dendrobatidae) from the eastern versant of the Central Cordillera of Colombia and the phylogenetic status of Colostethus fraterdanieli - Marin, Carlos M.; Molina-Zuluaga, Claudia; Restrepo, Adriana; Cano, Estefany; Daza, Juan M. (Zootaxa, 2018)
We describe a new species of Dendrobatidae from the eastern flank of the northern Central Cordillera in Colombia and assign it to the recently named genus Leucostethus. We also assess the phylogenetic status of the Colostethus fraterdanieli “complex” which according to our phylogenetic inference, is closely related to the new species. We use morphological, genetic and bioacoustic evidence to describe the new species and to expand the phylogeny of the genus Leucostethus. As a result, we transfer the content of C. fraterdanieli “complex” to Leucostethus. The new species differs from the Leucostethus fraterdanieli “complex” species by having white testes, straight pale ventrolateral stripes and high genetic divergence (17% in Cyt-b). According to our results, the genus Leucostethus is distributed in the western Amazonia from Ecuador and Peru, and both the northern Andes and Pacific lowlands in Colombia. We also found that L. fraterdanieli sensu stricto is restricted from mid (1600 m.a.s.l) to high (2500 m.a.s.l) elevation on the northern Central Cordillera in Antioquia. Extensive geographic sampling and more thorough morphological and bioacoustic examination need to be considered to solve the genetic clusters observed in the Leucostethus fraterdanieli “complex”.